Missouri Mathematics Project dalam Meningkatkan Kemampuan Penyelesaian Masalah Matematika Mahasiswa - Mawaddah, Sukma; Ahyansyah, Ahyansyah (Yayasan Pendidikan Intan Cendekia, 2022)
Solving mathematical problems is a scientific strategy in finding solutions to problems. The ability to solve problems is one of the abilities developed in Mathematics, this ability must also be possessed by everyone because it is closely related to daily life. The purpose of this study is to improve problem solving skills through the implementation of the Missouri Mathematics Project model. This research is a Class Action Research which includes 3 cycles. The study was conducted in a class of elementary school teacher candidates at a university in the Special Region of Yogyakarta. The instruments used were tests of mathematical problem-solving abilities and observation sheets of problem solving activities. Data analysis uses descriptive statistics. The results showed that in the first cycle the average acquisition rate of the group was 72, the average grade of the class was 57.8, and 67% of students were able to achieve a minimum grade. In the second cycle the average acquisition rate of the group was 74.8, the class average value is 52.4, and 56% of students are able to achieve a minimum grade. In the third cycle, the average acquisition rate was 82.4, the grade average grade is 72.7, and 77% of students are able to achieve a minimum grade. The results of the action showed an increase in students' ability to solve mathematical problems achieved in the third cycle.